2017
DOI: 10.1080/02688697.2017.1419163
|View full text |Cite
|
Sign up to set email alerts
|

Pilocytic astrocytoma of the cerebellopontine angle mimicking vestibular schwannoma: report of a rare entity

Abstract: We present a rare case of a 55-yr old patient of pilocytic astrocytoma of the cerebello-pontine angle mimicking a vestibular schwannoma. The tumor protruded into the porus acusticus causing enlargement of the internal auditory meatus, which is quite an unusual feature of glial tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…But in the present case, the primary tumor was located in the CPA. The case reported by Dutta et al 1 is similar to the one herein reported because of the size and imaging findings of the primary tumor, but it differs from our case due to the absence of evidence of CSF spread.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…But in the present case, the primary tumor was located in the CPA. The case reported by Dutta et al 1 is similar to the one herein reported because of the size and imaging findings of the primary tumor, but it differs from our case due to the absence of evidence of CSF spread.…”
Section: Discussionsupporting
confidence: 83%
“…Another theory is that the tumor originates primarily in the transformation of heterotopic neuroglial cell nests in the leptomeninges covering the proximal cranial nerves. 1 3 5 In the current case, there was no history of intraparenchymal glioma and no intraoperative evidence of an anatomic association to the lateral recess of the fourth ventricle. We believe that the tumor most probably originates from neuroglial cells.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Advanced neuroimaging techniques play a critical role in the evaluation of adult-onset PCAs. Magnetic resonance imaging (MRI) with contrast enhancement remains pivotal, providing detailed anatomical information and aiding in differential diagnosis [ 32 , 33 , 34 , 35 ]. Characteristic MRI features of PCA may include a cystic mass with a mural nodule and well-defined margins.…”
Section: Discussionmentioning
confidence: 99%
“…After an extensive Medline search, we could find only three cases of primary extra-axial pilocytic astrocytoma of the cerebellopontine angle (CPA) reported till now [1][2][3]. We recently encountered a right CPA pilocytic astrocytoma arising from the eighth cranial nerve, completely separated from the brain stem in a 23-yearold lady.…”
Section: Introductionmentioning
confidence: 99%